Adaptive menu: A review of adaptive user interface - Sushil Shrestha; Prashant Poudel; Siza Adhikari; Isha Adhikari (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
Intelligent User Interface (IUI) is an emerging interdisciplinary research area that focuses on improving the usability of existing user interfaces. Adaptive menus are the part of the IUI that is trying to improve existing menus' usability by reducing the selection time. This paper surveys the most relevant studies that are carried out in this field. First, it introduces an Adaptive User Interface (AUI) and adaptive menus then describe various adaptation styles and adaptation policies that are being used in adaptive menus along with their benefits and drawbacks. It then lists the applications of adaptive systems and how they can be used, as well as the limitations and future direction of the work.